Gas Permeability Test Protocol for Ion-Exchange Membranes - Park, Eun Joo; Komini Babu, Siddharth; Kim, Yu Seung (Frontiers in Energy Research, 2022)
The membrane-based electrolysis of water is a growing topic of interest due to the advantages of employing membranes in hydrogen production efficiency and system safety over the traditional alkaline water electrolysis. Ion-exchange membranes with low gas permeability are highly desirable for stable and safe operation of membrane-based water-splitting technologies, hence gas permeability through ion-exchange membranes needs to be properly assessed with standardized methods. We addressed three methods to measure gas permeability of ion-exchange membranes, a pressure permeation cell, chronoamperometry microelectrodes, and in situ testing of the membrane electrode assembly, and provide a guideline for choosing the appropriate method for the targeted operating conditions of the water electrolyzers.